Odpowiedzialność za naruszenie międzynarodowego prawa humanitarnego przez siły pokojowe Organizacji Narodów Zjednoczonych - Stochel, Jacek (Studia Prawa Publicznego, 2020)
Operations under the auspices of the Security Council mandate span over 70 years. Repeatedly involved in resolving armed conflicts, they have made a significant contribution to ensuring security and stability around the world. In practice, they have taken the form of operations by individual states, coalitions, other international organizations or simply as United Nations missions composed of contingents provided by Troop Contribution Countries (TCC). While operations under the auspices of the United Nations have been involved on several occasions in offensive activities under Chapter VII of the Charter of the United Nations, and the question of responsibility for these actions has been the subject of many legal analyses and judgments, missions organized by the United Nations are always recognized as neutral, and their activities as conciliatory and focused on monitoring the cessation of hostilities, or supervising the disengagement between the parties of the conflict, with the use of force limited to self-defence. Thus, such operations benefited from legal protection, and any action against them was considered a violation of international law. The current engagement of United Nations goes far beyond the traditional understanding of peacekeeping operations. UN missions are frequently authorized to employ all necessary means, up to and including the use of lethal force or even neutralization of the armed group. This creates a situation where in the light of International Humanitarian Law, such actions can be recognized as involvement in armed conflict. This article is intended to show the problems that the international community will soon face to in using United Nations’ missions as an instrument for resolving armed conflicts and as a tool for restoring peace and providing stability and security in the area of operations. It presents the processes of decision-making and subordination, which in some circumstances might result in the United Nations missions being deprived of legal protection and, in addition, made liable for non-compliance with the provisions of International Humanitarian Law.